Factores de riesgos maternos asociados al trabajo de parto pretérmino en gestantes de 18 a 25 años atendidas en el Hospital General León Becerra Camacho periodo octubre- abril 2023 - Tipanguano Quinatoa, Mónica Jissela (2023)
Establishing the risk factors associated with preterm labor is of vital importance in Ecuador because they are significantly related to this complication, where preterm birth has become the main cause of neonatal morbidity and mortality worldwide, where neonates They survive if they suffer from some type of physical, visual, cognitive disability, among others. The present study is transversal-quantitative, the purpose of which is to establish the maternal risk factors associated with preterm labor in pregnant women aged 18 to 25 years treated at the León Becerra Camacho General Hospital during the period October - April 2023. The analysis of the statistical data It is possible to demonstrate a higher incidence of preterm labor in the urban area with 66% and with a higher prevalence of percentages in pregnant women who presented low obstetric risk, for this reason as a theoretical proposal, it addresses in "Promote a hospital intervention plan that promotes health personnel about promotion and prevention measures with emphasis on sexual and reproductive health to reduce obstetric risk factors that produce preterm labor at the León Becerra Camacho General Hospital. whose purpose is for pregnant women to recognize the warning signs and maternal obstetric risk factors to prevent prenatal check-ups as soon as possible to avoid complications and thereby reduce maternal-fetal morbidity and mortality.